Leiomyoma of the round ligament in a postmenopausal woman: A rare case report. Issue 3 (15th October 2021) - Bhatti, Dimple; Mandrelle, Kavita; Chander, Ashima
Synopsis: Leiomyoma of the round ligament is a rare benign tumor that can be confused with an ovarian mass. Imaging and tumor markers can guide in the diagnosis.